SEGURANÇA ALIMENTAR EM ESCOLAS INDÍGENAS NA RELAÇÃO COM A CULTURA KAINGANG - Rios, Karina R.; Ribeiro, Marcos A.; Ubessi, Liamara D.; Espich, Caroline; Bellé, Tania R. L.; Bernard, Aline (Salão do Conhecimento, 2013)
Resumo